2021
DOI: 10.1186/s13256-020-02618-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 myopericarditis with cardiac tamponade in the absence of respiratory symptoms: a case report

Abstract: Background Previous reports have shown various cardiac complications to be associated with COVID-19 including: myocardial infarction, microembolic complications, myocardial injury, arrythmia, heart failure, coronary vasospasm, non-ischemic cardiomyopathy, stress (Takotsubo) cardiomyopathy, pericarditis and myocarditis. These COVID-19 cardiac complications were associated with respiratory symptoms. However, our case illustrates that COVID-19 myopericarditis with cardiac tamponade can present wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 7 publications
0
20
0
7
Order By: Relevance
“…Another myopericarditis case with large pericardial effusion and tamponade in patients with COVID-19 has been reported by Sauer et al too 4 . However, in comparison, Cairns et al reported an acute myopericarditis and pericardial effusion case, even in the absence of respiratory symptoms 19 .…”
Section: Review Of Literaturementioning
confidence: 96%
“…Another myopericarditis case with large pericardial effusion and tamponade in patients with COVID-19 has been reported by Sauer et al too 4 . However, in comparison, Cairns et al reported an acute myopericarditis and pericardial effusion case, even in the absence of respiratory symptoms 19 .…”
Section: Review Of Literaturementioning
confidence: 96%
“…Thirty two case reports describing a total of thirty three cases that document myocarditis/myopericarditis attributed to COVID-19 infection reported from July 1, 2020 to May 29, 2021 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Occurrence of myocarditis related to COVID-19 in males was higher than females (72.7%), and the median age of the reported cases was 49 years.…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 causes numerous cardiovascular complications including arrhythmia, myocarditis, acute myocardial injury, cardiogenic shock, and thromboembolism [ 12 , 13 ]. However, cardiac tamponade has rarely been reported as a COVID-19 complication [ 12 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial effusion was reported in 4.55% of 2738 patients with COVID-19 [ 15 ]. To date, only a few cases of pericardial effusion causing cardiac tamponade in patients with COVID-19 have been reported in the literature, and all of them were treated by pericardiocentesis, colchicine, pericardial window, aspirin, ibuprofen, steroids, and antiviral drugs [ 9 , 14 , 16 – 33 ]. Conversely, our case report demonstrates the first case treated by u-VATS.…”
Section: Discussionmentioning
confidence: 99%